A systematic review of the versatile effects of the Peruvian Maca Root (Lepidium meyenii ) on sexual dysfunction, menopausal symptoms and related conditions - Cherie Bower-Cargill; Niousha Yarandi; Andrea Petróczi (Elsevier, 2022)
Background: The Lepidium meyenii plant also known as Peruvian Maca, originates from high altitudes in the Andes, it has a high nutritional content and is extensively used as an herbal supplement for conditions such as sexual dysfunction, semen quality and menopausal symptoms. Objective: This systematic review was conducted to assess the effects of Maca on variety of conditions and not limited to sexual dysfunction, semen quality and menopausal symptoms. Methods: An extensive systematic review was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2015. Three databases (PubMed, Science Direct and Google Scholar) in addition to patents were searched up to March 2021. The key criteria for inclusion were; (1) in vivo study (2) randomized controlled clinical trial; (3) subjects were given Maca regardless of the type, preparation and/or administration route; and (4) measurable clinical data on a physiological and/or psychological aspect were reported. Studies were categorised into human and animal model studies and were further grouped by the type and preparation of Maca, dose, duration and condition assessed. The studies were also assessed for risk of bias according to the Cochrane Collaborations tool. Studies were compared to ascertain whether a meta-analysis was feasible. Results: A total of 57 studies, 14 clinical and 43 pre-clinical trials met the pre-defined criteria; although patent applications were searched none met the criteria. Nine different extraction methods of Maca were used with various coloured roots namely black, yellow and red roots or a mixture of all three. Different colour variations showed different effects thought to be due to the presence and/or concentration of secondary metabolites. Maca was reported to have an effect on conditions such as memory impairment, depression, bone structure, UV irradiations amongst others. Placebo and dose-dependant effects were observed in some studies. The overall quality of risk of bias was unclear due to insufficient information being published in addition to a high risk of reporting bias. Doses and durations varied, and an insufficient number of studies had further analysed whether these factors had an effect on the outcome made a meta-analysis unfeasible. Therefore, recommendations for future studies were discussed. Conclusion: Evidence to date suggests that Maca root could be an effective treatment for a range of conditions with 55 out of 57 studies reporting an effect. Clinical trials with rigorous reporting and methods are warranted.